2014
DOI: 10.2478/nsad-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Multicomponent Responsible Beverage Service Programme in Sweden – A Qualitative Study of Promoting and Hindering Factors

Abstract: AIMS -The objective of this study was to identify factors that either promote or hinder implementation of a multicomponent Responsible Beverage Service programme in Swedish municipalities. DESIGN -Forty semi-structured interviews were conducted in six municipalities and directed content analysis, guided by the Consolidated Framework for Implementation Research (CFIR), was performed. RESULTS -The CFIR framework was useful as an underlying theoretical model in this study. Importance of the following factors, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The studies we identified conceptualized, described or modelled systems of interest to alcohol-harm prevention research primarily in the United States (n = 38) [22,23,29,, Australia (n = 17) [28,31,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] and the United Kingdom (n = 7) [26,[92][93][94][95][96][97]. We also found examples of generic alcohol systems (n = 16) [24,93,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], as well as examples from Sweden (n = 2) [112,113], South Africa (n = 2) [114,115], Canada (n = 1) [116], Denmark (n = 1)…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The studies we identified conceptualized, described or modelled systems of interest to alcohol-harm prevention research primarily in the United States (n = 38) [22,23,29,, Australia (n = 17) [28,31,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] and the United Kingdom (n = 7) [26,[92][93][94][95][96][97]. We also found examples of generic alcohol systems (n = 16) [24,93,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], as well as examples from Sweden (n = 2) [112,113], South Africa (n = 2) [114,115], Canada (n = 1) [116], Denmark (n = 1)…”
Section: Resultsmentioning
confidence: 93%
“…A system is made up of interconnected elements bounded in some way within a broader context. Systems theory emphasizes the relationships between elements and understanding how different parts of the system interact and influence one another [36,128] Argument for systems-thinking lens in prevention and treatment efforts [71,108,109] Development of specific systems-informed approaches to interventions and programmes [57,71,85,113,117] Systems approach to drug and alcohol work-force development [106] and practitioner guidelines [102] Systems theory used to inform analytical framework [80,112,117,118] Complex adaptive systems and complexity theory A complex adaptive system (CAS) is made up of elements who interact with each other over time, without a central organizing authority, to generate behaviour at the system level that cannot be reduced to the actions of individual actors. Relationships within a CAS are non-linear and may be unpredictable, as elements and the system adapt and co-evolve in response to internal and external stimuli; responses within the system may amplify or dampen system changes, depending on the system's capacity to absorb or respond to change [129][130][131][132].…”
Section: Systems Theorymentioning
confidence: 99%
See 3 more Smart Citations